(untitled) (Journal of Economic Research & Business Administration, 2018)
Livestock development is one of the main strategic tasks of Kazakhstan’s economic and continues to be a major source of employment, food and income for the rural population. Analysis of current trends in the development of agrarian countries showed that the further development of the agro-industrial complex of Kazakhstan should focus on increasing the competitiveness of agricultural products by increasing the effectiveness of state support and creating equal favorable conditions for the development of agribusiness. In 2013, on behalf of the head of state NA. Nazarbayev The Government of the Republic of Kazakhstan has developed a “Concept for the formation of prospective national clusters of the Republic of Kazakhstan up to 2020”. In order to improve the regional policy of Akmola region in the sector of animal husbandry it is appropriate to consider the mechanism of association of all actors involved in the regional cluster meat specialization. This article describes a technique of forming a regional cluster in the example of the livestock industry of the Republic of Kazakhstan. Author’s technique consists of five successive phases. The authors suggest a comparison index of regional competitiveness, and the competitiveness of the livestock industry. Comparative analysis leads to the conclusion, in which areas of the republic is possible to create a cluster of livestock. The article is used a non-parametric statistical method of “Pattern” by which the calculated competitiveness factors. The authors attempt to adapt to the competitive assessment of the livestock industry.